EVALUATION OF SOME CUCUMBER FEMALE HYBRID F1 ( CUCUMIS SATIVUS L.) CULTIVARS GROWN UNDER THE CONDITIONS OF UNHEATED PLASTIC HOUSE IN THE MOSUL GOVERNORATE . - Mohammad AL-Habar; Hussien AL-Bayaty; Waleed A. (Mesopotamia Journal of Agriculture)
This study was conducted during Autum and Spring growing season 2010-2011 under conditions of unheated plastic house at the college of Agri. and Forestry, Mosul Univ.,to evalulate the performance of seven hybrid female cultivars : 1- Summit 2- Ameer 276 3- Grass 4- Baraa 5- Karol 6- Shadi 7-Laheeb . The results indicated `the superiety of Grass cv. in vegetative growth and quality traits which are : the length , diameter and mean weight of fruits in comparison with other cultivars . This cultivar was distinguished over the other cultivars in the total and marketable number of fruit / plant , early yield ( 9.977 and 14.123 ton / ha.) giving highest total yield (22.995 and 146.037 ton/ ha.) , and had a highest marketable yield ( 21.639 and 139.530 ton/ ha.) in both seasons respectively. Ameer and Summit cultivars revealed a good productivity( total and marketable yield ) in both seasons but the quality of their fruits did not reach the quality of Grass cultivar . The Karol cv. showed a good positive response in the total and marketable yield in spring season while its performance was very low in Autum. Shadi and Laheeb cultivars exhibited a decrease in the marketable yield in spring season as a result increasing the non-marketable yield . Baraa cv. resulted in unfavorable results in both seasons .